2011
DOI: 10.4081/oncol.2011.77
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pharmacokinetic determinants of anticancer kinase inhibitors in humans

Abstract: This review presents the published data regarding the molecular determinants (drug metabolizing enzymes, drug transporters and orphan nuclear receptors) of approved anticancer kinase inhibitors pharmacokinetics in humans. The clinical impact of these determinants (drug disposition and drug–drug interactions) is also discussed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…EGFR-TKIs cause a rapid decrease in target receptors by killing the EGFR mutation-harboring target cells, but objective evaluation of this phenomenon is thought to be difficult because systematic radiological evaluation of tumor size was not done in the early phase of treatment. Gefitinib has a longer t 1/2 and a larger tissue distribution than erlotinib [9,10]. Thus, the pharmacological parameters might be easily affected by the decreased number of target receptors.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR-TKIs cause a rapid decrease in target receptors by killing the EGFR mutation-harboring target cells, but objective evaluation of this phenomenon is thought to be difficult because systematic radiological evaluation of tumor size was not done in the early phase of treatment. Gefitinib has a longer t 1/2 and a larger tissue distribution than erlotinib [9,10]. Thus, the pharmacological parameters might be easily affected by the decreased number of target receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The initial oral cancer therapy agents, methotrexate and mercaptopurine, were approved in 1953 and have been obtainable in the United States for over half a century . To date, the number of oral cancer therapy drugs approved by the Food and Drug Administration has continued to increase, with more than 60 currently approved for use . Given the increasing incidence of cancer, it is expected that more patients will receive oral cancer treatment in the coming decades .…”
Section: Discussionmentioning
confidence: 99%
“…The number of orally available chemotherapy agents has significantly increased in the past decade, with more than 60 agents currently approved in the USA. 22 Additionally, 20%–30% of chemotherapy agents in the development pipeline will be administered orally. 23 Recent studies of the oral chemotherapy medication use process identified key vulnerabilities, including patient education about drug handling and adverse effects, prescription writing, monitoring, and toxicity management, and highlighted the need to adopt rigorous safety standards.…”
Section: Resultsmentioning
confidence: 99%